Structural reforms and the exchange rate regime: a panel analysis for the world versus OECD countries - Ansgar Belke; Bernhard Herz; Lukas Vogel (Institute for the Study of Labor (IZA), 2005)
We test the significance of the relationship between the exchange rate regime and the degree of structural reforms by estimating panel regressions for a world and an OECD country sample. The empirical results suggest a positive correlation between on the one side the adoption of an exchange rate rule and on the other side overall structural reforms as well as reforms in the money and banking sector in the broad country sample. For government size and for market regulation, we do not find any robust significant effect, however. The results do not confirm the main implication of Calmfors-type models, namely a higher degree of reforms under monetary policy autonomy. They corroborate conditional policy convergence and, partly, that limiting monetary policy autonomy fosters structural reforms.
Keywords: D78; E52; E61; 330; exchange rates; monetary policy regime; liberalisation; panel data; political economy of reform; Wechselkurssystem; Wirtschaftsreform; Schätzung; Welt; OECD-Staaten